Unveiling individuality in the early phase of motor learning: a machine learning approach for analysing weightlifting technique in novices - Ammar, Achraf; Simak, Marvin Leonard; Salem, Atef; Horst, Fabian; Schöllhorn, Wolfgang Immanuel (Frontiers in Bioengineering and Biotechnology, 2024)
Despite the growing body of evidence highlighting the individuality in movement techniques, predominant models of motor learning, particularly during the acquisition phase, continue to emphasise generalised, person-independent approaches. Biomechanical studies, coupled with machine learning approaches, have demonstrated the uniqueness of movement techniques exhibited by individuals. However, this evidence predominantly pertains to already stabilised movement techniques, particularly evident in cyclic daily activities such as walking, running, or cycling, as well as in expert-level sports movements. This study aims to evaluate the hypothesis of individuality in whole-body movements necessitating intricate coordination and strength among novice participants at the very beginning of an acquisition phase. In a within-subject design, sixteen highly active male participants (mean age: 23.1±2.1 years), all absolute novices in the learning task (i.e., power snatch of Olympic weightlifting), participated in randomised snatch learning bouts. These bouts comprised 36 trials across various motor learning models: differential learning (DL), contextual interference (serial, sCIL; and blocked, bCIL), and repetitive learning (RL). Kinematic and kinetic data were collected from three standardised snatch trials performed following each motor learning model bout. The time-continuous data were input to a linear Support Vector Machine (SVM). We conducted analyses on two classification tasks: participant and motor learning model. The SVM classification revealed a notably superior participant classification compared to the motor learning model classification, with an averaged prediction accuracy of 78% (≈ 32 of 41 snatch trials) versus 27.3% (≈ 9 of 36 snatch trials). In specific fold and input combinations, accuracies of 91% versus 38% were respectively achieved. Methodically, the crucial role of selecting appropriate data pre-processing methods and identifying the optimal combinations of SVM data inputs is discussed in the context of future research. Our findings provide initial support for a dominance of individuality over motor learning models in movement techniques during the early phase of acquisition in Olympic weightlifting power snatch.